An Assessment of the economic and social impacts of climate change on the tourism sector in the Caribbean - Moore, Winston [et al] (UN New YorkUS, 2013)
Uses information on historic and future Caribbean climate data to calculate that the region's tourism climatic index (TCI) ranges from -20 (impossible) to +100 (ideal). Suggests that climatic conditions in the Caribbean under both the A2 and B2 climate scenarios of the Intergovernmental Panel on Climate Change (IPCC) expected ti deteriorate, and are likely to become less conducive to tourism; and more specifically that the greatest decline in the TCI is likely to occur during the northern hemisphere summer months from May to September. Indicates also that home conditions during the traditional tourist season (December - April) are likely to improve, which could make it more attractive for visitors from these markets to consider 'staycations' as an alternative to overseas trips.